Comparative Study of Knowledge and Attitudes of Rural-Urban Households on Polio Vaccination in Northeast Nigeria - Hussaini Ibn Mohammed; Aisa Isa Geidam (International Journal of Children, 2026)
Poliomyelitis (polio), although it has been eradicated over the decades, continues to be a major problem of public health in Nigeria. Polio vaccination is the best way to counteract the transmission of poliovirus, although differences in knowledge and attitude to polio vaccination between rural and urban families are present and especially in Northeast Nigeria. This paper explores such differences, evaluates their impact on the knowledge, attitudes, and acceptance of polio vaccinations, based on the household location. A sample of 400 households (200 rural and 200 urban) was picked using a comparative cross-sectional survey design among the states of Borno, Yobe, and Adamawa using a multistage sampling method. Structured questionnaires were used to collect data which were analyzed by using descriptive and inferential statistics. The results have shown that urban households possess much more knowledge regarding polio and immunization schedules than rural households. Favourable views of vaccination were also found in urban and rural settings the latter being less inclined to take the vaccine and more influenced by cultural beliefs, misunderstandings of vaccine safety, and lack of health-care access. Other aspects like level of education, availability of healthcare centres and exposure to awareness programs were all found to have positive correlations with knowledge and acceptance of polio vaccination. The conclusions of the study are that despite the increase in the awareness in the country due to national vaccination campaigns, there is need to implement target interventions that focus on addressing rural-specific barriers, such as community engagement, education, and better service delivery, which are necessary to support equitable vaccine coverage and maintain polio eradication efforts in Northeast Nigeria.
Keywords: Knowledge; Northeast Nigeria; attitudes; polio vaccination; poliomyelitis; rural households; urban households